Creativity and resilience: a mini-review on post-pandemic resources for adolescents and young adults - De Lorenzo, Aurelia; Lattke, Lynda S.; Rabaglietti, Emanuela (Frontiers in Public Health, 2023)
Two years after the outbreak of the pandemic, several studies look at the consequences for the well-being and mental health of young people. In particular, creativity and resilience are cited in the scientific literature as resources that promote this well-being in adolescents and young adults. This mini-literature review was created with the aim of examining how many articles have explored the relationship between creativity and resilience in adolescents and young adults since the onset of the pandemic. Particular attention was paid to how many of the articles actually related to the consequences of the pandemic, in which country they were published, their target population, and the models, instruments and variables used to analyze them. Only 4 articles emerged from the screening, of which only one was actually related to pandemic consequences. All articles were published in Asian countries with a target group of university students. Three of the articles used mediation models to examine the relationship between resilience as an independent variable and creativity as a dependent variable. All articles used self-assessment instruments for creativity and resilience, both at the individual and group level. This mini-review offers us the opportunity to reflect on the lack of studies that have addressed the issue of youth resources in the form of creativity and resilience since the beginning of the pandemic. The results show us a still underdeveloped interest in the scientific literature, contrary to what the media tells us.